T2 : infiltrator - Stirling, S. M. (New York : EOS, 2009)
The Cyberdyne Corporation is back in business and a new kind of terminator, a "female" who understands human thought and emotion, hunts Sarah Connor and her son John, who are hiding from the U.S. government in Paraguay.
"Based on the world created in the motion picture written by James Cameron and William Wisher."
Publisher's Weekly
Adult.
Adult
Keywords: Robots -- Fiction; Time travel -- Fiction; Robots -- Fiction; Science fiction; Time travel -- Fiction; Paraguay -- Fiction; Paraguay -- Fiction; Science fiction